Pengaruh Financial Literacy, Financial Self-Efficacy, Locus of Control, Parental Income, Love of Money terhadap Financial Management Behavior: Lifestyle sebagai Mediasi - Mawalia Ulumudiniati; Nadia Asandimitra (Jurnal Ilmu Manajemen, 2022)
Thrifty can be used as an indication that someone has good financial management behavior. This research aims to investigate the influence of financial literacy, financial self-efficacy, locus of control, parental income, love of money on financial management behavior and lifestyle as mediating variables of Z Generation Thriftier in East Java. The type of research used is quantitative conclusive causality, and data analysis technique used Structural Equation Model (SEM) with Amos 24 software. The number of samples obtained was 264 respondents by using purposive and snowball sampling techniques and taken from an online questionnaire. The findings show that there is no influence of parental income on financial management behavior, but there is an influence of financial literacy, financial self-efficacy, locus of control, love of money and lifestyle on financial management behavior. In addition, financial literacy influences lifestyle, and lifestyle mediate between financial literacy and financial management behavior. Therefore, the results of this research can be contributed as a reference for all parties, especially Z Generation Thriftier in East Java to improve their skills, abilities and responsibilities for making the right financial decisions and managing their finances better.